EUROPEAN INTEGRATION AND INDEPENDENCE OF CENTRAL BANKS - KOZIUK, Viktor (Journal of European Economy, 2025)
The 1990s and 2000s were marked by a global trend towards greater central bank independence. Were the institutional trajectories of strengthening such independence the same in European countries? Grouping countries according to the criterion of when they joined the EU demonstrated significant intergroup differences in the behavior of the central bank independence index proposed by Romelli (2024). The «old» EU countries, due to historical traditions, were less homogeneous with a lower level of independence at the beginning but turned out to have a higher level of independence and more homogeneous later, thanks to stricter requirements for membership in the eurozone. The countries of the «new» EU initially reformed their central banks in line with the logic of market transformation and only intensified reforms before joining the EU, remaining a less homogeneous group. For Central and Eastern European countries, the inverse relationship between the level of central bank independence and inflation could be questioned due to exogenous pressure to strengthen such independence due to European integration requirements. However, it does exist, confirming the established theoretical view. Also, the existence of an inverse relationship between inflation and the index of central bank independence is evidence that European integration alone cannot substitute for the status of monetary authorities. JEL: E02, E58, F15, F45